Storage stability of pasteurized buko juice in doy packs - Clavecilla, Christine B.
ABSTRACT This research study is an observation of the storage stability of pasteurized buko juice in DOY packs. Coconut water (sabaw ng buko) from coconuts aged 7-8 months (malakanin stage) was utilized together with weighed amounts of refined white sugar and blended coconut meat to prepare buko juice with the most acceptable water-to-water ratio.This ratio was found to be 80:20 based on the results of CAT using ANOVA and DMRT at 5% level of significance. The buko juice was pasteurized at three sets of pasteurization time and temperature to effectively destroy the harmful, spoilage-causing microorganisms that could be present in the formulated buko juice. Microbiological analysis reported 0 cfu/ml on plate count agar for both the TPC and YMC while it showed negative with the Coliform test. However, the buko juice pasteurized at 80°C for 5 seconds was most favored based on sensory analysis. After pasteurization, the buko juice was aseptically filled into the DOY packs which were sealed immediately using an electric sealer. The sealed DOY packs were cooled to 25-30°C in a water bath and placed under three different storage temperatures. The buko juice stored under room temperature (15-35°C) deteriorated on its 2nd day, accompanied with bulging of the DOY pack. The buko juice stored under refrigerated temperature (10-15°C) was reported to have <250 cfu/ml on its 3rd week using the TPC while the buko juice stored under freezing temperature (-5°C and below) reached the same microbial content later on its 4th week. Physico-chemical and sensory analyses done on a regular weekly basis also showed that the buko juice in DOY packs was more stable under freezing temperature than under refrigerated temperat